Anxiety Trajectories in Adolescents and the Impact of Social Support and Peer Victimization - Spence, Susan H.; Lawrence, Lawrence; Zubrick, Stephen R (My University, 2022)
This paper examines whether adolescents can be reliably categorized into subgroups based on their patterns of anxiety levels over time and whether low levels of social support from parents, peers, and their school, and high levels of peer victimization, predict a pattern of increasing anxiety. Participants were 3392 youth from the Longitudinal Study of Australia's Children (LSAC). Youth-reported anxiety was measured at three occasions at ages 12/13 years, 14/15 years, and 16/17 years, with social support and victimization assessed at age 12/13 years. Anxiety trajectories were identified using latent class growth mixture modelling, and predictors of class membership were examined using multinomial logistic regression analyses. Three discrete classes of anxiety trajectories were identified. Most youth fell within a stable-low anxiety symptom class (89.5% males; 78.2% females), with smaller percentages in low-increasing (5.6% males; 14.4% females) or high-decreasing (4.9% males; 7.4% females) classes. Low support from parents and teachers, low sense of school belonging, and high peer victimization predicted membership of the low-increasing anxiety trajectory class, irrespective of gender. Social support did not moderate the effect of peer victimization upon the risk of developing anxiety, with peer victimization remaining a risk factor even when adolescents experienced good social support from parents, peers, and school. The findings highlight the need for screening in early adolescence to identify those who are experiencing low social support and high peer victimization and are thus at increased risk of developing anxiety problems. These youth could then be offered targeted intervention to reduce the likelihood of anxiety development.
Research in Child and Adolescent Psychopathology
Keywords: Adolescents and youth; Health and wellbeing